Analysis of Employer Branding and Digital HR Practices on Employee Performance Agility Through Employee Engagement - Navy Septiya Ningrum; Mesra B; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2026)
This study aims to examine the effect of Employer Branding and Digital HR Practices on Performance Agility through Employee Engagement among employees of PT Permodalan Nasional Madani (PNM) Medan. A quantitative approach with a survey method was employed in this research. The population consisted of 50 employees, and all members of the population were selected as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that Employer Branding and Digital HR Practices have a positive and significant effect on Employee Engagement. Furthermore, Employer Branding, Digital HR Practices, and Employee Engagement positively and significantly affect Performance Agility. The mediation analysis reveals that Employee Engagement significantly mediates the relationship between Employer Branding and Performance Agility as well as between Digital HR Practices and Performance Agility. These findings suggest that improving employee performance agility can be achieved through strengthening employer branding, optimizing digital HR practices, and enhancing employee engagement. This study provides practical implications for organizations in developing adaptive human resource management strategies to cope with dynamic workplace changes.